Circlize package in R and Analytic Hierarchy Process - Shen, Gangxu; Wang, Wei-Lung (PloS one, 2022)
The morphological diversity of floral organs can largely be attributed to functional divergence in the MADS-box gene family. Nonetheless, research based on the ABCDE model has yet to conclusively determine whether the AGAMOUS-LIKE 6 (AGL6) subgroup has a direct influence on floral organ development. In the current study, the ABCDE model was used to quantify the contributions of ABCDE and AGL6 genes in the emergence of floral organs. We determined that the flower formation contribution values of the ABCDE and AGL6 genes were as follows: A gene, 0.192; B gene, 0.231; CD gene, 0.192; E gene, 0.385; and AGL6, 0.077. As AGL6 does not directly influence floral structure formation, the contribution value of AGL6 to flower formation was low. Furthermore, the gradient values of the floral organs were as follows: sepals, 0.572; petals, 1.606; stamens, 2.409; and carpels, 2.288. We also performed detailed analysis of the ABCDE and AGL6 genes using the Circlize package in R. Our results suggest that these genes likely emerged in one of two orders: 1) B genes[right arrow]CD genes[right arrow]AGL6[right arrow]E genes[right arrow]A genes; or 2) B genes[right arrow]CD genes[right arrow]AGL6/E genes[right arrow]A genes. We use the analytic hierarchy process (AHP) to prove the contribution values and gradient values of floral organs. This is the first study to understand the contribution values of ABCDE and AGL6 genes using the AHP and the Circlize package in R.